Hepatology and Transplant Hepatology A Case Based Approach - Ahmad, Jawad; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2011)
Hepatology and Transplant Hepatology: A Case Based Approach presents a collection of interesting cases in liver disease seen at a very busy and large liver transplant center in the United States. These cases cover the full range of pathology that an internist or gastroenterologist may expect to see in a lifetime of taking care of patients with acute or chronic liver disease, before or after liver transplant. Each case is presented as you would see it in a clinical situation where a patient presents a complaint or something is noted on exam or blood work. The question/answer format will help one through the problem of making a diagnosis or in considering a differential diagnosis and also point to the best way to manage each condition. The volume is divided into pre-transplant and post-transplant hepatology. Each case is 3 pages with the first page presenting the case and pertinent lab data and 3-4 questions (i.e. differential diagnosis, tests to order, x-rays/CT required).The second page illustrates the tests, scans, biopsies and asks for the pertinent findings. The third page provides the diagnosis and what may have been expected with other diagnoses. Here is a single source dealing with questions specific for patients with complications of advanced liver disease and also clinical situations seen in transplant hepatology. Hepatology and Transplant Hepatology: A Case Based Approach will have great appeal to anyone in hepatology/transplant hepatology and also to residents/fellows and internists interested in gastroenterology.
Section 1. General Hepatology: Cases 1-26 -- Section 2. Advanced Liver Disease: Cases 27-65 -- Section 3. Transplant Hepatology: Cases 66-90.
Keywords: Medicine; Internal medicine; Gastroenterology; Clinical medicine; Medicine & Public Health; Hepatology; Gastroenterology; Internal Medicine